On $(h,m)$-Convex Functions and Inequalities - Valdés, Lucas Gómez, Juan E. Nápoles (Discontinuity, Nonlinearity, and Complexity, 2026)
This work explores novel integral inequalities for $(h,m)$-convex functions using key mathematical techniques, including Hölder's, Young's and Power Mean inequalities. By leveraging these classical results, we establish improved bounds and extend Hermite-Hadamard type inequalities. The findings contribute to a deeper understanding of $(h,m)$-convex functions and their role in mathematical analysis. Additionally, we discuss particular cases to emphasize the relevance of our contributions.